Engaging the millennial first-year teacher education learner: A preliminary case study - Dobozy, Eva; Martin, Romana (LAMS Foundation, 2008)
Teaching practices grounded in constructivist learning theories run counter to the dominant highly structured and lecturer-controlled approaches to learning and teaching in which the lecturer transmits established, accumulated information for students to learn and reproduce, largely through one or two hour lectures followed by practical tutorial exercises. Consequently, university lecturers interested in adopting constructivist approaches to university learning and teaching will have to successfully negotiate a set of challenges that have been described as conceptual, pedagogical, cultural, and political. In this paper, we briefly explore the principles of humanist learning and teaching as we understand them. This is followed by an illustration of our pedagogical responses to the needs of millennial first-year teacher education learners, many of whom demand to be active, hands-on, practical and supported by peers, tutors and lecturers on a ‘just-in-time’ basis. In particular, we report some preliminary findings from our LAMS pilot with first-year teacher education students. They confirm earlier observations that note that many first-year university students seem to possess the emotional maturity, cognitive and interpersonal skills necessary for student-centred technology-enhanced learning and teaching, but others do not. Finally, we discuss possible directions for better integrated learning environments that provide adequate support to millennial first-year teacher education students to enable their meaningful engagement and participation in online learning conversations with their peers.